Experimentation of the Asy-Shafi'i Method on the Ability to Read the Qur'an in View of Student Interests: Eksperimentasi Metode Asy-Syafi’i Terhadap Kemampuan Membaca Al-Qur’an Ditinjau dari Minat Mahasiswa - Astuti, Robia; Nurmitasari, Nurmitasari; Khasanah, Binti Anisaul; Efendi, Rahmat (Halaqa: Islamic Education Journal, 2023)
The background of this research is that there are still many UMPRI students, especially students in the FKIP mathematics education study program who cannot read the Al-Qur’an properly. In reading the Qur'an there are many factors that influence it, one of which is student interest. The purpose of this study was to find out whether students who learn to read the Al-Qur’an using the Asy-Syafi'i method have better reading skills than students who do not use the Asy-Syafi'i method in terms of student interest. This research is a quasi-experimental study with a 2x3 factorial design. The population in this study were all students of the Mathematics Education Study Program, FKIP UMPRI, for the 2022-2023 academic year. The research sample was obtained by means of cluster random sampling. Data analysis techniques use non-parametric statistics because the population is not normally distributed. The results showed that the ability of students to read the Al-Qur’an using the Asy-Syafii method was better than the ability of students to read the Koran who did not use the Asy-Syafii method. However, there is no difference in the ability to read the Al-Qur’an between students who have high, medium or low interest in reading the Al-Qur’an or are equally good.